(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To identify factors associated with eating disorders in children with attention deficit hyperactivity disorder. Methods: A cross-sectional descriptive study was conducted on 246 children aged 6-12 years diagnosed with attention deficit hyperactivity disorder at Bach Mai Hospital and Vietnam National Children’s Hospital from November 1, 2025, to March 30, 2026. Results: Eating disorders were identified in 17.9% of children with attention deficit hyperactivity disorder. Univariable analysis showed that eating disorders were associated with malnutrition, sensory processing disorders, psychiatric comorbidities, age at onset below 3 years, age at diagnosis of 7 years or older, and the combined clinical presentation. In the multivariable logistic regression model, age at onset below 3 years, age at diagnosis of 7 years or older, malnutrition, and psychiatric comorbidities were independent factors associated with eating disorders. Among these factors, malnutrition and delayed diagnosis showed the strongest associations. Conclusion: The findings suggest that screening for eating-related problems should be integrated into the comprehensive assessment and management of children with attention deficit hyperactivity disorder to facilitate early detection and timely intervention.